(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Alzheimer Disease (AD), the most prevalent form of dementia in the world, is a progressive neurological condition that lowers quality of life and puts a strain on carers. Several linked comorbidities as well as social and risk factors can be addressed and controlled, if necessary, despite the fact that the condition cannot be totally prevented with current medication. Aim: Our study makes an effort to define and clarify the relative frequency of these characteristics in patients who present with AD vs those who present with other neurologic issues. Methods: This study comprised 324 cases of Alzheimer's disease, including 208 men and 116 women. Results: The findings indicate etiologic variables and chances for prompt intervention. Diabetes, hyperlipidemia, cerebrovascular illness, and depression are substantially linked with dementia. The association between hypertension and dietary factors, occupational factors, or marital status was insignificant. The study's total aged population with its prevalent comorbidities and confounding variables is one of its limitations. Conclusion: In order to prevent or delay the onset of dementia, this study concludes that it is crucial to address modifiable risk factors.